2017
DOI: 10.1016/j.fm.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy evaluation of a new water sanitizer for increasing the shelf life of Southern Australian King George Whiting and Tasmanian Atlantic Salmon fillets

Abstract: The bacterial species and specific spoilage organisms associated with the Southern Australian King George Whiting (KGW) and Tasmanian Atlantic Salmon (TAS), and the efficacy of a HOCl-containing water-based sanitization product (Electro-Chemically Activated Solution, by ECAS4) in extending the shelf life of KGW and TAS fillets were evaluated. Fillets were washed with an ECAS4 solution containing either 45 ppm or 150 ppm of free chlorine and bacterial species enumerated on selective and non-selective media, fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…The initial bacterial reduction of 0.67 Log 10 CFU/m 3 after fogging for one hour is comparable to that achieved in our previous study, where Ecas4 anolyte at 45 ppm FAC wash sanitisation of fish fillets achieved reduction of 0.5 Log 10 [18]. Likewise, the 1.34 Log 10 CFU/m 3 reduction after two hours of fogging was superior to washing fish fillets with 150 ppm FAC (1.0 Log 10 ) [18].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The initial bacterial reduction of 0.67 Log 10 CFU/m 3 after fogging for one hour is comparable to that achieved in our previous study, where Ecas4 anolyte at 45 ppm FAC wash sanitisation of fish fillets achieved reduction of 0.5 Log 10 [18]. Likewise, the 1.34 Log 10 CFU/m 3 reduction after two hours of fogging was superior to washing fish fillets with 150 ppm FAC (1.0 Log 10 ) [18].…”
Section: Discussionsupporting
confidence: 86%
“…The initial bacterial reduction of 0.67 Log 10 CFU/m 3 after fogging for one hour is comparable to that achieved in our previous study, where Ecas4 anolyte at 45 ppm FAC wash sanitisation of fish fillets achieved reduction of 0.5 Log 10 [18]. Likewise, the 1.34 Log 10 CFU/m 3 reduction after two hours of fogging was superior to washing fish fillets with 150 ppm FAC (1.0 Log 10 ) [18]. The different effectiveness observed between the two fish fillet wash experiments and the two fogging time points could be attributed to the presence of organic matter quenching the anolyte active components, since even Ecas4 with low FAC (0.5 ppm) was able to totally inactivate bacterial cells (5 Log 10 ) in the absence of organic material.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results suggest that the presence of organic matter on pork limits the efficacy of NEW against Salmonella Typhi and mesophilic bacteria. In our study, NEW was applied using spray bottles however, different studies 42,46 showed better results when samples were dipped.…”
Section: Resultsmentioning
confidence: 70%
“…Of the various types of EOW, neutral EOW has been considered the most promising as it contains predominantly HOCl, which is more effective than ClO − for microbial cell wall penetration and oxidative attack 12,17 . However, there are limited published applications of neutral EOW use in the irrigation and washing of fresh vegetables 18,19 or fruit 20,21 , with publications to date mainly focussing on its use in the seafood 22 and meat 17,23,24 industries. The use of Na-based salts rather than K for generation of the EOW might be of concern in the context of vegetable production, because of the potential problems associated with Na accumulation in soil, in contrast to the potential benefit of K supplementation for crop growth.…”
Section: Introductionmentioning
confidence: 99%